Analisis Pengaruh Strategi Pemasaran Terhadap Peningkatan Jumlah Nasabah Asuransi Bumiputera Di Medan - Anisa Bella Saragih; Zainarti (CV. ITTC INDONESIA, 2024)
This study aims to analyze the impact of marketing strategies on increasing the number of policyholders at BUMIPUTERA insurance company in Medan. In the increasingly competitive insurance industry, companies are required to design effective marketing strategies to attract potential customers and retain existing ones. This research employs a qualitative approach using in-depth interviews with 10 respondents, consisting of policyholders and potential customers of BUMIPUTERA insurance in Medan. The data analysis is conducted through thematic analysis, focusing on a deep understanding of the influence of various marketing strategy elements, such as promotion, communication, product development, and distribution, on customers’ decisions to choose insurance products. The results of the study show that marketing strategies involving effective promotions, the use of social media, andimproved service quality significantly affect customers’ decisions to join the company. Additionally, respondents emphasized the importance of developing products that meet the needs of the community, especially in terms of flexibility and benefits offered. The study also reveals that the close relationship between insurance agents and customers, as well as transparent communication, are key factors in building trust and customer loyalty. In conclusion, appropriate marketing strategies can significantly increase the number of policyholders at BUMIPUTERA insurance in Medan and support the company’s long-term growth.